2023
DOI: 10.1098/rsif.2023.0021
|View full text |Cite
|
Sign up to set email alerts
|

The three-dimensional coarse-graining formulation of interacting elastohydrodynamic filaments and multi-body microhydrodynamics

Abstract: Elastic filaments are vital to biological, physical and engineering systems, from cilia driving fluid in the lungs to artificial swimmers and micro-robotics. Simulating slender structures requires intricate balance of elastic, body, active and hydrodynamic moments, all in three dimensions. Here, we present a generalized three-dimensional (3D) coarse-graining formulation that is efficient, simple-to-implement, readily extendable and usable for a wide array of applications. Our method allows for simulation of co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…By relaxing the assumption that all lateral movement directions are uniformly distributed, we introduce the possibility of looping patterns into the movement. We present this as a discrete alternative to the model of 'chiral' persistent motion [30,[61][62][63], where an angular bias is introduced into the turning angle, which is of interest as a model of a charged particle subjected to soft scattering by aligned magnetic domains [30] and particles driven by microscopic torques such as active colloids [64], spermatozoa [65], and chlamydomonas [66]. While chiral motion appears at first to lend itself to a continuous space representation, it is known that even the two-dimensional case leads to an analytical intractable Fokker-Planck equation [30], meaning occupation probabilities and further transport quantities are difficult to obtain.…”
Section: Chiral Motionmentioning
confidence: 99%
“…By relaxing the assumption that all lateral movement directions are uniformly distributed, we introduce the possibility of looping patterns into the movement. We present this as a discrete alternative to the model of 'chiral' persistent motion [30,[61][62][63], where an angular bias is introduced into the turning angle, which is of interest as a model of a charged particle subjected to soft scattering by aligned magnetic domains [30] and particles driven by microscopic torques such as active colloids [64], spermatozoa [65], and chlamydomonas [66]. While chiral motion appears at first to lend itself to a continuous space representation, it is known that even the two-dimensional case leads to an analytical intractable Fokker-Planck equation [30], meaning occupation probabilities and further transport quantities are difficult to obtain.…”
Section: Chiral Motionmentioning
confidence: 99%
“…Metachronal coordination has been shown to improve the flow generation and energetic efficiency of cilia [5,6] and is found across a wide range of species, from swimming protozoa [7,8], Volvox algal colonies [9,10] and coral larvae [11] to ependymal surfaces in brain ventricles [12] and respiratory epithelia [13]. Theoretical models [5,[14][15][16][17][18][19][20][21] and experimental studies [10,22] have demonstrated that hydrodynamic interactions can explain the synchronization of two or more cilia or flagella. Other studies also point to the role of intracellular basal linkages [23][24][25], probably acting in synergy with fluid-mediated coupling.…”
Section: Introductionmentioning
confidence: 99%